Analysis of Accountability and Transparency of Village Fund Allocation Management in Sebani Village, Pandaan District, Pasuruan Regency - Devia Nur Anggreani; Siti Rohmawati; Nabillah Mutiara Rahma; Umi Setyorini; Ufi Rumefi (HM Journals, 2024)
The village as the smallest government system demands renewal to support improved village development and the standard of living of village communities that are far from poverty. The various problems in the village are very complex, making it a reason for the village to develop. The development progress in each village is no less important. This research aims to analyze accountability and transparency of village fund allocation management in Sebani Village, Pandaan District, Pasuruan Regency. The method in this study is a descriptive qualitative method by means of direct interviews with informants. The location of this accountability and transparency research is in Sebani Village, Pandaan District, Pasuruan Regency. This research was carried out for a period of 6 months, starting from January 2024 to June 2024. The data is processed using data analysis techniques with stages, namely data reduction, data presentation, and drawing conclusions. The results of the study based on the Regulation of the Minister of Home Affairs Number 20 of 2018 show that the management of village fund allocations in Sebani Village is accountable and transparent in the stages of administration, reporting, and accountability.